Neutrophil-to-Lymphocyte Ratio and Systemic Inflammation Index as Predictors of Poor Outcome in Patients with Critical Limb Ischemia Treated with Remote Endarterectomy - Derșidan Anca Alexandra; Ciucanu Claudiu Constantin; Ilioniu Agatha Maria; Bodiu Ionela Georgiana; Covalcic Carina Diana; Szanto Ludovic Alexandru; Mureșan Adrian Vasile (Journal of Cardiovascular Emergencies, 2022)
Introduction: Severe ischemia occurring in the lower limbs represents the advanced stage of peripheral artery disease (PAD). Atherosclerosis and inflammatory markers have been intensively studied to identify prognostic tools with a role in the evolution of patients with PAD. The aim of this study is to demonstrate the predictive value of systemic inflammatory markers such as the neutrophil-to-lymphocyte ratio (NLR) and the systemic inflammation index (SII) in the prognosis of patients diagnosed with critical leg ischemia (CLI) undergoing infrainguinal surgical revascularization with remote endarterectomy.